Competence, human values, and career planning as joint drivers of individual performance: Evidence from KPP Pratama Jakarta Pasar Minggu - Ariyani, Natalina (Privietlab, 2025)
This study tests whether three human-capital levers—employee competence, internalization of core public-service values, and career planning—jointly predict individual performance in a frontline Indonesian tax office (KPP Pratama Jakarta Pasar Minggu). Anchored to the Ministry of Finance’s Balanced Scorecard architecture, performance is operationalized in line with Nilai Kinerja Pegawai (NKP), combining target attainment (CKP) and multi-rater behavioral scores. Using a cross-sectional survey of structural and functional staff, we validated scales for the three predictors and estimated their effects on performance. Bivariate correlations show the strongest association for competence (r ≈ 0.54), followed by career planning (r ≈ 0.37) and the human values system (r ≈ 0.30). In multivariate models, the trio explains ≈41.6% of variance in NKP, with competence emerging as the most influential single predictor while values and career planning add distinct, meaningful contributions. Descriptives point to high endorsement of ethical conduct and service behaviors, yet signal headroom in feedback, reward fairness, and structured career pathways. Managerially, a dual track is clear: deepen role-specific competence (case-based learning, coaching, job aids) and operationalize values and career scaffolding (transparent recognition, “learn-from-mistakes” routines, formal IDPs and rotations) through the NKP review cadence. These interventions align systemically with how performance is actually measured and rewarded, improving both throughput and citizen experience.